Dietary black soldier fly oil enhances growth performance, flesh quality, and health status of largemouth bass (Micropterus salmoides) - Hailin Yuan; Junru Hu; Xiangce Li; Qiuxuan Sun; Xiaohong Tan; Cuihong You; Yewei Dong; Yanhua Huang; Meng Zhou (Animal Nutrition)
The study aimed to assess the effects of dietary black soldier fly oil (BSFO) on the growth performance, flesh quality, and health status of largemouth bass (Micropterus salmoides). Six iso-nitrogenous and isolipid diets were formulated by substituting fish oil and soybean oil (1/2, wt/wt) with BSFO in percentages of 0%, 20%, 40%, 60%, 80%, and 100%, respectively. The diets were fed to 960 fish (initial body weight = 16.5 g) in four replicates for 8 weeks. Indicators related to growth performance, body composition, hematology, flesh quality, expression of genes related to inflammatory cytokines and apoptosis, and the response of fish to Aeromonas veronii challenge were analyzed. The results showed that the weight gain rate was numerically improved in all BSFO substitution groups, ranging from 9.3% to 44.0% compared to the control group. The highest survival rate and the lowest hepatosomatic index and condition factor were observed in the BFSO20 group. In terms of flesh quality, the water-holding capacity of the dorsal muscle was elevated with higher levels of dietary BSFO. However, significant changes in texture properties (cohesiveness, gluing, and chewiness) were observed in the BSFO20 group (P < 0.05). Six hematological parameters related to glycolipid and liver function were optimized in most of the BFSO substitution groups. Furthermore, the expressions of six inflammation- and apoptosis-related genes (IL-1β, Bcl-xl, BAX, caspase8, TNF-α, and IL-10) were significantly affected by dietary BSFO (P < 0.05). Following bacterial challenge, the seven-day cumulative survival rates of fish were considerably increased from 10.0% in the control group to 60.0% and 66.7% in the BSFO80 and BSFO100 groups, respectively. One-variable linear regression analysis revealed that various parameters related to fish growth, flesh quality, and health status were significantly influenced by dietary BSFO substitution levels in a dose-dependent manner (P < 0.05). In conclusion, substituting around 20% of dietary fish oil and soybean oil with BSFO is promising in improving the growth performance and flesh quality of M. salmoides. However, to enhance immunity and disease resistance, it is recommended to further increase the inclusion of BSFO in the diet.